Examining regional disparities in child malnutrition: insights from Maharashtra India - Rushikesh Khadse; Rufi Shaikh (Journal of Health, Population and Nutrition)
Abstract Background Malnutrition poses a significant challenge at the national level in developing countries like India, where the state-level situation varies considerably. Therefore, this study aims to investigate child nutrition across different geographical regions of Maharashtra and assess inequalities in child malnutrition. Methods Utilizing data from the National Family Health Survey (2019-21), the study employs univariate, bivariate, and Concentration Index statistical techniques for analysis. Result The findings reveal a decrease in the prevalence of stunting, wasting, and underweight, with North Maharashtra exhibiting an alarming situation regarding underweight children. The study underscores the importance of dietary patterns as crucial determinants in reducing malnutrition prevalence, highlighting factors such as initial breastfeeding practices and bottle feeding. Notably, malnutrition is predominantly concentrated among poor households in Maharashtra. Conclusion Overall, the study concludes that while there has been a declining trend in the prevalence of malnutrition over time, there has been no change observed in the most recent survey rounds. Factors such as household wealth, maternal education, and dietary patterns are strongly associated with the nutritional status of children. The importance of investigating the factors contributing to the stagnation in malnutrition reduction observed in recent survey rounds. Efforts should be directed towards addressing these underlying issues to effectively combat malnutrition.